Nonparametric estimation of an additive model with a link function - Joel L. Horowitz; Enno Mammen (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
This paper describes an estimator of the additive components of a nonparametric additive model with a known link function. When the additive components are twice continuously differentiable, the estimator is asymptotically normally distributed with a rate of convergence in probability of n -2/5 . This is true regardless of the (finite) dimension of the explanatory variable. Thus, in contrast to the existing asymptotically normal estimator, the new estimator has no curse of dimensionality. Moreover, the asymptotic distribution of each additive component is the same as it would be if the other components were known with certainty.
urn:nbn:de:kobv:11-10049252
Keywords: 330; nonparametric regression; additive models; multivariate curve estimation; kernel estimates; orthogonal series estimator